DIPLOMASI EKONOMI INDONESIA TERHADAP BRASIL DALAM MENINGKATKAN EKSPOR MINYAK NABATI PERIODE 2017 - 2021 - Al Bahits Annef, (2022)
The dynamics of international relations in recent years have had a substantial impact on global trade conditions. The Indonesian government has adopted an adaptive policy on developing exports to non-traditional markets. Latin America Region is selected as one of the export-development, with Brazil as the largest economic powerhouse in the region. At the same time, Indonesian export on vegetable oil, which consisting of palm oil (HS 1511) and coconut oil (HS 1513) as the leading products to Brazil experienced a declining exports trend up to -11% in the period of 2016-2020. There is an urgency to utilize economic diplomacy in order to overcome the challenges and capture the opportunities. By using descriptive qualitative research methods with simple trade calculations, this study aims to analyse Indonesia's economic diplomacy model to non-traditional markets with a case study of increasing vegetable oil exports to Brazil. This study also uses international trade theory and non-traditional market concepts as a basis for analysis. The authors' findings are that there are 6 driving factors for the implementation of diplomacy, 3 execution actors for conducting economic diplomacy and 8 processes of economic diplomacy. From orientation perspective, specific efforts to encourage vegetable oil exports were identified as minimum. However, in terms of output, with the rejuvenating Indonesian economy situation in 2021 and encouraged by economic diplomacy instruments has resulted to a successful acceleration on vegetable oil exports to Brazil in the period of 2017-2021.